THE INFLUENCE OF SERVICE QUALITY AND MEDICAL FACILITIES ON PATIENT SATISFACTION AND ITS IMPLICATIONS FOR PATIENT LOYALTY AT PULANG PISAU REGIONAL HOSPITAL, CENTRAL KALIMANTAN - Santi Sandra; Kosasih; Taufan Nugroho; Farida Yuliaty; Vip Paramarta; Fitriana (RADJA PUBLIKA, 2025)
This study aims to explain the quality of service, medical facilities, patient satisfaction, and patient loyalty at Pulang Pisau Regional General Hospital, Central Kalimantan, and to analyze the direct and indirect influence of service quality and medical facilities on patient satisfaction and their implications for patient loyalty. This research employed a descriptive method to map the condition of each variable and a verificative method with a quantitative approach to test research hypotheses. The findings indicate that service quality and medical facilities are categorized as good and statistically have a positive and significant influence on patient satisfaction. Partially, service quality and medical facilities significantly improve patient satisfaction, while simultaneous testing shows a synergistic interaction of both variables in predicting satisfaction. The direct path analysis reveals that only medical facilities have a significant direct effect on loyalty, while service quality requires mediation. Furthermore, the mediation analysis shows that patient satisfaction facilitates the transmission of positive effects from both variables toward loyalty, making satisfaction a bridging variable that strengthens the relationship between service quality, medical facilities, and patient loyalty. These findings indicate that patient satisfaction functions as a crucial and fundamental mediator that consolidates the contributions of service quality and medical facilities in building sustainable patient loyalty.